PSYCHOPEDAGOGICAL WORK WITH PARENTS IN OPERATIVE GROUPS - Siqueira Santos , Cristiane (Revista Gênero e Interdisciplinaridade, 2022)
This article discusses a research with qualitative approach where the study is to present an account of an experience operating group, shows the adventure of living the group, to coordinate it, observe it and provoke you so that we can learn to live and build new relationships between parents and their children, which aims to present partial results of a study and investigate how the technique of operating group created by Pichón-Rivière, having the prospect of going through a school space in order to modify the relations between parents and children. As specific goal to understand how an operating group may cooperate and transform the education of children. The results show that the group intervention is a strategy that allowed address the subjective and intersubjective dimension of the participants. The school environment can be understood as a space of diversity of beings and of thoughts, where bloom a series of questions.